Formulation of Cinnamon (Cinnamomum verum) oil loaded solid lipid nanoparticles and evaluation of its antibacterial activity against Multi-drug Resistant Escherichia coli - Mehran Nemattalab; Masoumeh Rohani; Mehdi Evazalipour; Zahra Hesari (BMC, 2022)
Abstract Today, the increment in microbial resistance has guided the researches focus into new antimicrobial compounds or transmission systems. Escherichia coli (E. coli) is an opportunistic pathogen, producing a biofilm responsible for a wide range of nosocomial infections which are often difficult to eradicate with available antibiotics. On the other hand, Cinnamomum verum (cinnamon oil) (CO) is widely used as a natural antibacterial agent and Solid lipid nanoparticles (SLNs) are promising carriers for antibacterial compounds due to their lipophilic nature and ease of transmission through the bacterial cell wall. In this study, nanoparticles containing cinnamon oil (CO-SLN) were prepared by dual emulsion method and evaluated in terms of particle size, shape, entrapment efficiency (EE), transmission electron microscopy (TEM), oil release kinetics, and cell compatibility. The antibacterial activity of CO-SLN and CO against 10 drug-resistant E. coli strains was investigated. The anti-biofilm activity of CO-SLN on the selected pathogen was also investigated. Nanoparticles with an average size of 337.6 nm, and zeta potential of -26.6 mV were fabricated and their round shape was confirmed by TEM images. The antibacterial effects of CO-SLN and CO were reported with MIC Value of 60-75 µg/mL and 155-165 µg/mL and MBC value of 220-235 µg/ml and 540-560 µg/ml, respectively. On the other hand, CO-SLN with 1/2 MIC concentration had the greatest inhibition of biofilm formation in 24 h of incubation (55.25%). The data presented indicate that the MIC of CO-SLN has significantly reduced and it seems that SLN has facilitated and promoted CO transmission through the cell membrane.